An investigation into how the European Working Time Directive has affected anaesthetic training - Bowhay, Andrew R (BioMed Central, 2008)
BACKGROUND: The European Working Time Directive (EWTD) became law in 1993 but only applied to doctors in training in the United Kingdom in 2004. The trainees have in consequence had a reduction in their working hours but also a change to a shift pattern of working. For craft specialities, such as anaesthesia, there are concerns that a reduction in working hours has also led to a reduction in the time available for learning and that ultimately this may affect patient care. However, there is scant research on the perceptions of trainees concerning the impact of the EWTD on their training and working lives. This study investigated what the anaesthetic Specialist Registrars (SpRs) on the Mersey Deanery SpR rotation perceived to be training and also what effect the EWTD has had on that training and their quality of life, both within and outside work. METHODS: The project was a cross sectional survey, using a quantitative questionnaire with qualitative free text comments which were aggregated into overarching themes and sub themes. RESULTS: 117 SpRs were sent questionnaires in April 2005; 73 completed questionnaires were returned (response rate 62.4%). Hierarchies of training opportunities emerged with training by consultants being most valued. 71.8% (95% CI 60.7 – 81.3) of trainees believed the EWTD has had a deleterious effect on their training and experience and 74.3% (95% CI 63.2 – 83.4) thought that they will be less prepared for a consultant post. 69.9% (95% CI 58.7 – 79.5) considered that their quality of life outside work had deteriorated, with only 15% (95% CI 8.3 – 24.6) finding improvement. 38.6% (95% CI 27.8 – 50.3) felt that they were not functioning as well as doctors, only 14.3% (95% CI 7.6 – 23.9) noting improvement. The trainees were still positive about anaesthesia and 73.2% (95% CI 62.2 – 82.5) would recommend this specialty to a student. CONCLUSION: The majority of anaesthetic SpRs in the Mersey Deanery have not welcomed the changes brought by the EWTD to their training, experience and quality of life outside work.